(E)-3-(3-Methylthiophen-2-yl)-1-p-tolylprop-2-en-1-one - S. Naveen; Helmi Muhammed Al-Maqtari; Joazaizulfazli Jamalis; Hasnah Mohd Sirat; N. K. Lokanath; Muneer Abdoh (IUCrData, 2017)
In the title compound, C15H14OS, the dihedral angle between the thiophene and benzene rings is 31.34 (13)°. The thiophene S atom and enone C=O group are approximately in an anti orientation. In the crystal, molecules are linked via pairs of very weak C—H-...O hydrogen bonds, forming inversion dimers with R22(16) ring motifs.